Matriptase‐1 expression is lost in psoriatic skin lesions and is downregulated by TNFα in vitro. (29th October 2015) - Mildner, Michael; Bauer, Reinhard; Mlitz, Veronika; Ballaun, Claudia; Tschachler, Erwin
Summary: Background and objectives: Matriptase‐1 participates in terminal keratinocyte (KC) differentiation. Knockdown of matriptase‐1 in skin equivalent cultures leads to impaired KC differentiation and retention of nuclei in the stratum corneum. Here, we investigated the expression and regulation of matriptase‐1 in psoriatic skin and in KC in vitro. Patients and methods: Matriptase‐1 expression in healthy and psoriatic skin and its regulation in skin equivalents were analyzed by Western blotting, immunofluorescence staining, qRT‐PCR, and activity assays. Involvement of the nuclear factor kappa B (NFκB) signaling pathway was investigated by adenoviral overexpression of a dominant‐negative form of IKK2. Results: Matriptase‐1 expression was detected in the stratum granulosum of healthy human skin and in skin equivalent cultures. Its expression and activity was strongly reduced in lesional skin of patients with psoriasis. Addition of TNFα to skin equivalent cultures resulted in complete loss of matriptase‐1 expression accompanied by disturbed KC differentiation. Mechanistically, we were able to show that TNFα‐induced downregulation of matriptase‐1 was inhibited by blocking the IKK2/NFκB signaling pathway. Conclusions: Given that matriptase‐1 participates in terminal KC differentiation, its absence in psoriatic skin lesions indicates that this contributes to the barrier disturbances in this disease. Our data suggests that blocking the IKK2/NFκB‐pathway represents a potential target for the treatment of psoriasis.